IN VITRO ASSESSMENT OF ANTIOXIDANT AND ANTICANCER ACTIVITIES IN MURRAYA KOENIGII (L.): A PHYTOCHEMICAL APPROACH - DEBAPRIYA SUBHADARSHAN BEHERA; NIHAR RANJAN KAR (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study presents phytochemical screening and in vitro assessment of antioxidant and anticancer activity of Murraya koenigii (L.) leaf extract and isolated molecule MKLE-01. Methods: The ethanol extract was screened for phytochemical analysis by phytochemical screening tests. The antioxidant activity of ethanol extract of M. koenigii and isolated compounds (MKLE-01) was evaluated by the 1-diphenyl-2-picrylhydrazyl method, and anticancer activity was carried out by the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-tetrazolium bromide (MTT) assay method. Results: The phytochemical screening of ethanol extract showed the presence of flavonoids, alkaloids, glycosides, phytosterols, and glycosides. In terms of their antioxidant activity, our findings demonstrated the ethanolic extracts’ significant in vitro free-radical scavenging capabilities. The extract and isolated compound half maximal inhibitory concentration (IC50) values of antioxidant activity were found at 154±0.202 μg/mL and 53±0.002 μg/mL, respectively. In comparison with cisplatin (IC50=6±0.001 μg/mL), ethanol extract revealed a moderate and dose-dependent growth diminution of breast cancer cells in the MTT assay at dosages over 100 μg/mL, with an IC50 of 72±0.023 μg/mL. The isolated compound displayed a significant effect with an IC50 of 34±0.002 μg/mL. Conclusion: The results we obtained demonstrate that isolated compounds and ethanolic extract could represent promising anticancer agents and effective antioxidants.